Adaptive robust optimization for European strategic gas infrastructure planning. (15th October 2022) - Riepin, Iegor; Schmidt, Matthew; Baringo, Luis; Müsgens, Felix
Abstract: The European natural gas market is undergoing fundamental changes that foster uncertainty on both supply and demand sides. This uncertainty has elicited questions about the value of the Projects of Common Interest—strategic infrastructure investments supported by public funding from the European Union. This paper addresses this matter by deploying the adaptive robust optimization framework to consider long-term uncertainties in the gas infrastructure expansion planning problem. This framework confronts the drawbacks of mainstream methods of incorporating uncertainty in gas market models, such as stochastic scenario trees, in which the modeler predefines the probabilities and realization paths of unknown parameters. Our mathematical model endogenously identifies the unfortunate realizations of unknown parameters and suggests the optimal investment strategies to address them. We use this feature to assess which Projects of Common Interest are valuable in maintaining system resilience amid cold-winter demand spikes and supply shortages, while also considering budget constraints. The robust solutions indicate consistent preferences for specific projects. We find that real-world construction efforts have been focused on the most promising projects from a business perspective. However, we also find that the vast majority of projects are unlikely to be realized without financial support, even if they would serve as a hedge against stresses in the European gas system. Highlights: An adaptive robust optimization model for a gas transmission expansion problem. Analysis of Projects of Common Interests' value in maintaining gas system resilience. Endogenous realizations of cold-winter demand spikes and supply shortages. Publicly available source code for the entire project.